Digital Deposit Services at Commercial Banks and their Accounting Ways - Abdug’aniev Muhammadamin Abdug’affor o’g’li (International Journal of Scientific Trends, 2024)
In this article, digital deposit in commercial banks of the Republic of Uzbekistan in recent years a number of practical works to further develop and increase the scope of servicesconclusions are presented.